2016
DOI: 10.1016/j.jaci.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death ligand 1 alleviates psoriatic inflammation by suppressing IL-17A production from programmed cell death 1–high T cells

Abstract: PD-1 is overexpressed in IL-17A-producing T cells in both imiquimod-treated mice and patients with psoriasis. Moreover, recombinant PD-L1-Fc alleviates psoriatic inflammation in imiquimod-treated mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 33 publications
(45 reference statements)
4
57
0
Order By: Relevance
“…Both γδ T cells and CD4 + Th17 cells are IL-17-producing effector cells that drive human psoriasis and the IMQ-induced model of psoriasiform inflammation 10,1214 . To investigate the contribution of γδ T cells and CD4 + Th17 cells during the development of psoriasiform inflammation in the Vsir −/− mice, we first examined their cell number in the ear and ear-draining LN.…”
Section: Resultsmentioning
confidence: 99%
“…Both γδ T cells and CD4 + Th17 cells are IL-17-producing effector cells that drive human psoriasis and the IMQ-induced model of psoriasiform inflammation 10,1214 . To investigate the contribution of γδ T cells and CD4 + Th17 cells during the development of psoriasiform inflammation in the Vsir −/− mice, we first examined their cell number in the ear and ear-draining LN.…”
Section: Resultsmentioning
confidence: 99%
“…21 The same authors observed similar results in the skin of psoriatic patients in whom immunofluorescent staining also revealed an overexpression of PD-1 on IL-17A-producing T cells.…”
mentioning
confidence: 54%
“…It has been shown to contribute to the accumulation of IL-6 and GCSF as well as cardiotoxicity induced by DOX. [16][17][18].…”
Section: Discussionmentioning
confidence: 99%